Pharmacological activities and mechanisms of proteins and peptides derived from traditional Chinese medicine - Yadi Ni; Yuya Zhu; Lingxin Xu; Jin’ao Duan; Ping Xiao (Science of Traditional Chinese Medicine)
Abstract. Proteins and peptides are important active components of traditional Chinese medicine (TCM) widely found in plants, animals, and fungi. Modern research indicates that the protein constituents of TCM possess various pharmacological activities, including antitumor effect, immunomodulation, antioxidation, antihypertension, anti-inflammation, cardiovascular and nervous system protection, blood sugar regulation, and bacteriostasis effects. Despite significant progress in recent years regarding the pharmacological activities and mechanisms of TCM components, research on protein components of TCM has lagged. Many TCM protein components have yet to be effectively developed, and their pharmacological activities and mechanisms remain insufficiently elucidated. This article provides a comprehensive review of the pharmacological activities and mechanisms of TCM proteins and peptides. Additionally, the current shortcomings in research are discussed to offer some insights, aiming to promote further investigation of TCM proteins and peptides and facilitate their application in new drug development and clinical treatment.